2003
DOI: 10.1046/j.1432-1033.2003.03708.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the serotoninergic system in the C57BL/6 mouse skin

Abstract: We showed expression of the tryptophan hydroxylase gene and of tryptophan hydroxylase protein immunoreactivity in mouse skin and skin cells. Extracts from skin and melanocyte samples acetylated serotonin to N-acetylserotonin and tryptamine to N-acetyltryptamine. A different enzyme from arylalkylamine N-acetyltransferase mediated this reaction, as this gene was defective in the C57BL6 mouse, coding predominantly for a protein without enzymatic activity. Serotonin (but not tryptamine) acetylation varied accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 48 publications
6
127
1
Order By: Relevance
“…Adrenals were obtained from Wistar rats killed under anesthesia. Male rats aged 3 months were obtained from the vivarium of the Department of Biotestings of Bioorganic Chemistry Institute (Minsk, Belarus) (detailed protocols were described previously) [21]. The Institutional Animal Care and Use Committee at AMC approved the original protocol, and a similar protocol for mice was approved at UTHSC; for LC/MS assays the experiments were approved by the Belarus University Animal Care and Use Committee.…”
Section: Biological Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenals were obtained from Wistar rats killed under anesthesia. Male rats aged 3 months were obtained from the vivarium of the Department of Biotestings of Bioorganic Chemistry Institute (Minsk, Belarus) (detailed protocols were described previously) [21]. The Institutional Animal Care and Use Committee at AMC approved the original protocol, and a similar protocol for mice was approved at UTHSC; for LC/MS assays the experiments were approved by the Belarus University Animal Care and Use Committee.…”
Section: Biological Materialsmentioning
confidence: 99%
“…The methodology followed standard protocols described in our laboratories [21,31]. Briefly, mitochondrial fractions prepared as described above for detection of P450scc or adrenodoxin reductase or proteins extracted with 1% (v/v) Triton X-100 (to test StAR expression) from placenta, skin or cultured cells were dissolved in Laemmli buffer and separated on an SDS/12% polyacrylamide gel, transferred to an Immobilon P [poly(vinylidene difluoride)] membrane (Millipore Corp, Bedford, MA, USA); nonspecific binding sites were blocked by incubation in 5% (w/v) nonfat powdered milk in buffer containing 50 mM Tris/HCl, pH 7.5, 150 mM NaCl, and 0.01% (v/v) Tween-20, for 3 h at room temperature.…”
Section: Western Blottingmentioning
confidence: 99%
“…1) ( 5 ). This included detection of the genes and proteins for tryptophan hydroxylase (TPH), serotonin N-acetyl-transferase (NAS), and hydroxyindole-O-methyltransferase (HIOMT) in the whole skin and skin cells, and actual demonstration of the corresponding enzymatic activities ( [23][24][25][26][27][28] ).…”
Section: Cutaneous Pathway For Melatonin Synthesismentioning
confidence: 99%
“…NAS can in fact be produced in the C57BL/6 mouse strain ( 25 ), which represents natural AANAT "knockdown" ( 33 ), through an alternate pathway ( 5,25 ). NAS produced in the skin may be released into the circulation ( 5 ), and could be transformed into melatonin after delivery to organs expressing HIOMT ( 34 ).…”
Section: Cutaneous Pathway For Melatonin Synthesismentioning
confidence: 99%
“…It was was reported that human melanoma cells can synthesize and metabolize serotonin [119]. Later, a characterization of the serotonergic system in the C57BL/6 mouse skin was presented emphasizing that mouse skin has the molecular and biochemical apparatus necessary to produce and metabolize serotonin and N-acetylserotonin [137]. Furthermore, the immunofluorescence of skin biopsies tended to localize TPH protein and serotonin immunoreactivity to normal and malignant melanocytes in vivo, and the cutaneous pathway for local serotonin synthesis in melanocytes was also reported [138,142], implicating the skin as a target of bioregulation by serotonin.…”
Section: The Pharmacology Of Serotonin Receptorsmentioning
confidence: 99%